Sedentary behaviour among elderly patients after total knee arthroplasty and its influencing factors - Xuan Ni; Juan Shi; Qing Hu; Ai Li; Xing Zeng; Yajing Gu (Scientific Reports, 2024)
Abstract To understand the status of sedentary behaviour in elderly patients after total knee arthroplasty and analyse its influencing factors so as to provide a reference for developing targeted interventions. Conveniently selected elderly patients undergoing total knee arthroplasty (> 6 months) in a tertiary hospital in Jiangsu Province were investigated using a general information questionnaire, the Charlson Comorbidity Index, patients’ self-reported sedentary behaviour information, the WOMAC Score, The Groningen Orthopaedic Social Support Scale, and Lee’s Fatigue. The median daily sedentary time was 5.5 h (4.5 h, 6.625 h) in 166 elderly patients after total knee arthroplasty, of whom 82 (49.40%) showed sedentary behaviour (≥ 6 h per day). Logistic regression analysis showed that being retired/unemployed (OR = 8.550, 95% CI 1.732–42.207, P = 0.0084), having a CCI score ≥ 3 (OR = 9.018, 95% CI 1.288–63.119, P < 0.0001), having high WOMAC scores (OR = 1.783, 95% CI 1.419–2.238, P < 0.0001), having a high social support score (OR = 1.155, 95% CI 1.031–1.294, P = 0.0130), and having a fatigue score ≥ 5 (OR = 4.848, 95% CI 1.084–21.682, P = 0.0389) made patients more likely to be sedentary. The sedentary time of elderly patients after total knee arthroplasty is long, and sedentary behaviour is common among them. Healthcare professionals should develop targeted sedentary behaviour interventions based on the influencing factors of sedentary behaviour in order to reduce the occurrence of sedentary behaviour in elderly patients after total knee arthroplasty.